2014
DOI: 10.1002/ppsc.201400078
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive Gold Polymer Nanohybrids with a Tunable Cross‐Linked MEO2MA Polymer Shell

Abstract: Gold nanoparticles (AuNPs) are functionalized with a thermoresponsive polymer shell of a cross‐linked poly(2‐(2‐methoxyethoxy)ethyl methacrylate) (P(MEO2MA)). To provide a covalent attachment of the polymer to the NP surface, AuNPs are first modified using butanoic acid to develop the encapsulation with the biocompatible thermoresponsive polymer formed by free‐radical precipitation polymerization. Both the MEO2MA concentration and the shell cross‐linking density can be varied and, in turn, the thickness and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Smart polymers can be chosen to exhibit stimuli-responsive properties whereby their structure is strongly affected by the external conditions ( e.g . light, temperature, pH, concentration of chemicals, pressure or electronic fields) 1 5 . Among them, thermoresponsive polymers have gained a great deal of attention since the phase transition between hydrophilic and hydrophobic states involves a considerable change in volume when reaching a lower critical solution temperature (LCST) 6 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Smart polymers can be chosen to exhibit stimuli-responsive properties whereby their structure is strongly affected by the external conditions ( e.g . light, temperature, pH, concentration of chemicals, pressure or electronic fields) 1 5 . Among them, thermoresponsive polymers have gained a great deal of attention since the phase transition between hydrophilic and hydrophobic states involves a considerable change in volume when reaching a lower critical solution temperature (LCST) 6 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Contreras-Cáceres et al (2009) have reported that, if Au and BIS content are kept constant, then the VPTT of Au-p(NIPAM) hybrid microgels increases from 36°C to 42°C by decreasing the feed content of NIPAM from 100% to 40%. Lapresta-Fernández et al (2014) have observed that the VPTT of hybrid microgels decreases by increasing the content of cross-linker tetraethylene glycol dimethacrylate. According to the best of our knowledge, the modulation of the VPTT of negative thermoresponsive Au-microgels by varying the content of Au nanostructures has not been reported in the literature yet.…”
Section: Negative Temperature-responsive Behaviormentioning
confidence: 94%
“…” This principle includes ANHs composed of metallic, carbonaceous or polymeric NMs and NHs functionalized with stimuli-responsive coronas or polymers [ 47 , 48 , 49 , 50 ] ( Figure 1 a) and NMs suspended or loaded with linear and branched stimuli-responsive co-polymers or cross-linked polymer networks [ 35 , 51 , 52 ] ( Figure 1 b). ANHs in which stimuli-responsive coatings are covalently bonded to drug molecules [ 53 ] or to metallic NMs with tunable properties [ 25 ] ( Figure 1 c) and polymer brushes grafted [ 54 ] or strongly bonded via sulfur bonds [ 47 ] can also be included.…”
Section: Principle For Discerning Anhsmentioning
confidence: 99%
“…The thermo-responsive coating undergoes a phase transition from a hydrophilic water-swollen state to a hydrophobic globular state, when heated above its LCST. Such changes result in modification of the light scattering properties of the nano-system and cause a change in the turbidity of the gel network of PMEO2MA [ 25 ]. Different degrees of swelling at high and low temperatures influence the range of applications of core-shell ANHs.…”
Section: Classification Of Anhsmentioning
confidence: 99%
See 1 more Smart Citation